2019
DOI: 10.1371/journal.pone.0211021
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic comparison of the barbell deadlift using constant versus variable resistance in healthy, trained men

Abstract: Variable, external resistance is proposed to increasingly augment the muscular stress throughout a dynamic movement. However, it is uncertain how different levels of variable resistance affect the activation in the deadlift. The aim of the study was to compare the electromyographic activity of the gluteus maximus, biceps femoris, semitendinosus, vastus lateralis and erector spinae muscles during the barbell deadlift with free weights (FW) alone, with two (FW-2EB), and four elastic bands (FW-4EB) to deload some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 19 publications
5
31
0
Order By: Relevance
“…In relation to free-weight exercises, the greatest activation was found on the deadlift (barbell deadlift:~90% MVIC; hex bar deadlift:~80% MVIC) and hip-thrust exercise (~85% MVIC) [46]. Also, the back squat performed until failure and 2RM deadlift reported the highest mV values (~0.35 mV) [28,40].…”
Section: Erector Spinaementioning
confidence: 98%
See 1 more Smart Citation
“…In relation to free-weight exercises, the greatest activation was found on the deadlift (barbell deadlift:~90% MVIC; hex bar deadlift:~80% MVIC) and hip-thrust exercise (~85% MVIC) [46]. Also, the back squat performed until failure and 2RM deadlift reported the highest mV values (~0.35 mV) [28,40].…”
Section: Erector Spinaementioning
confidence: 98%
“…The participant, in a standing position with feet shoulder-width apart, has to lower the body in order to lift the barbell until the hip is fully extended while maintaining a neutral spine position. This exercise may vary depending on specific protocols (e.g., Romanian deadlift, stiff leg, hexagonal bar deadlift) [40,44,46].…”
Section: Deadliftmentioning
confidence: 99%
“…In contrast to Galpin et al they found the variable resistance to increase the force, but reduce the velocity when compared to free weights. Finally, only one study has compared free weight deadlift with assisted deadlift (Andersen et al, 2019 ). Andersen et al ( 2019 ) compared muscle activation in the hamstring, gluteus, and erector spinae muscles between 2 RM in free weights vs. free weights in combination with either a high or a low contribution from elastic bands among resistance-trained men.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, only one study has compared free weight deadlift with assisted deadlift (Andersen et al, 2019 ). Andersen et al ( 2019 ) compared muscle activation in the hamstring, gluteus, and erector spinae muscles between 2 RM in free weights vs. free weights in combination with either a high or a low contribution from elastic bands among resistance-trained men. The results showed a higher activation in the erector spinae, favoring the high assistance condition when compared to the low assisted condition, but with no difference to the free weights.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation